STRATEGI PUBLIC RELATIONS DALAM MENANGANI COMPLAIN CUSTOMER - Dian Hutami Rahmawati; Latif Ahmad Fauzan; Winih Mega Handika; Yulinar Luthfiyah Prastiyasti (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Efforts to handle all forms of input from service users of PT. Angkasa Pura is a priority for companies to improve their capabilities. Given the COVID-19 pandemic, various groups have felt the impact. This makes PT. Angkasa Pura carries out several policy considerations, as well as evaluations that are in line with existing conditions in the field. Of course, with this evaluation, there are several problems related to comfort due to the features of airport facilities that are not felt by the company, even the service users of PT. Angkasa Pura. This research was conducted offline at Sultan Aji Muhammad Sulaiman Sepinggan Airport Balikpapan, to be precise at PT Angkasa Pura Balikpapan Septenver 2021. In this study, the research sample or subject of this study was Public Relations Team of PT. Angkasa Pura, namely the Head of Public Relations of PT. Angkasa Pura. Data were obtained from in-depth interviews and obtained directly from informants who were at the research site. The results of the study concluded that related to the PR strategy carried out by PT. Angkasa Pura is providing voting rights from service users regarding complaints about the company through various platforms that make it easier for service users, this is given by the company not only as a forum for complaints but also as a form so that companies can participate in conveying more detailed information. related to the company, also conducts 2-way communication to its communicants.